THE EUROPEAN UNION (EU) AND THE CLIMATE-SECURITY NEXUS: CSDP MISSIONS AND OPERATIONS - Ayfer Genç Yılmaz (Ankara Avrupa Çalışmaları Dergisi)
Since the mid-2000s, the climate-security nexus has come to the forefront of scholarly debates. For some scholars, the linkages between climate change and security should be analyzed from the national security perspective, whereas others from a human security perspective. Taking into consideration the implications of climate change on national and human security, international organizations worldwide started to develop policies in this field. The EU acknowledges climaterelated security risks and searches for new policies and tools to respond to them. Yet, the EU’s efforts remain mainly at the discursive level. On the practical level, the EU’s various policy tools have not yet incorporated climate-security nexus in their agenda. This paper aims to analyze the impact of the climate-security nexus on the EU’s CSDP missions and operations.